Evaluating surface smoothness of composite film of well-dispersed silica particles. (2nd September 2022) - Wen, Quanyue; Tanahashi, Fumiya; Fuji, Masayoshi
ABSTRACT: The surface smoothness of a composite film of polyimide and silica particles was evaluated by changing the dielectric constant based on the gap between the film surface and electrode surface. The silica particles were modified by different treatments, then mixed with the polyimide to prepare the particle composite films. The experimental results showed that even in the films with well-dispersed particles, a more suitable dispersion state exists based on the surface roughness. Moreover, an increase in the surface smoothness of the film will increase the dielectric constant of the composite films. The feasibility of this new evaluation method was confirmed after evaluating films with different smoothness and the results of the film surface smoothness scans were compared. This method allows for a fast, large-scale determination of samples and is independent of the film transparency.